FINANCIAL RATIO AND DIVIDEND POLICY OF COMPANY LISTED ON INDONESIAN STOCK EXCHANGE YEAR 2006-2008 - Sri Sumariyati; Henny Medyawati (Jurnal Ilmiah Ekonomi Bisnis, 2012)
The determination of dividend policy is influenced by two factors: financial and nonfinancial factors. The study focuses more on financial aspects that directly describe the condition of a company. The purpose of the study is thus to examine the effect of financial ratios which are consists of Return on Investment (ROI), Cash Ratio, Debt to Equity Ratio (DER), and Earning per Share (EPS) on dividend policy. Dividend policy was measured using Dividend Payout Ratio (DPR). Result shows that ROI, CR, DER and EPS significantly influence DPR simultaneously. Partially, DER shows dominant influence on DPR.Key Words : Return on Investment, Cash Ratio, Debt to Equty Ratio, Earning per Share, Dividend Payout Ratio